003.5 Clinician-taken extra-genital samples for gonorrhoea and chlamydia in women compared with self-taken samples analysed separately and self-taken pooled samples. (13th September 2015) - Wilson, JD; Wallace, HE; Fisher, J; Ward, H; Hulme, C; Wilcox, MH
Abstract : Background: Extra-genital sampling (rectum and pharynx) using nucleic acid amplification tests is becoming increasingly important in women as vulvovaginal swabs (VVS) alone may miss infections. We compared clinician-taken extra-genital samples in women with self-taken samples analysed both separately and as pooled samples for accuracy and cost-effectiveness. Methods: Women attending a sexual health clinic were invited into a 'swab yourself' trial. Clinician and two self-samples (analysed separately and pooled) were taken from vulvovaginal, pharyngeal and rectal sites for gonorrhoea (NG) and chlamydia (CT) using AC2. Sampling order was randomised. Patient infected status was defined as at least two positive confirmed samples. Results: 402 women recruited January–March 2015. Overall prevalence: gonorrhoea 3.2% (rectal 2.7%, pharyngeal 1.5%), chlamydia 13.7% (rectal 12.9%, pharyngeal 3.2%). One NG case (7.7%) and 7 CT cases (12.7%) were VVS negative. McNemar test showed no difference between clinician-taken and self-taken rectal or pharyngeal samples, or between self-taken samples analysed separately or pooled. Conclusion: This on-going work is the first randomised study showing women's self-taken extra-genital samples are comparable to clinician-taken and can be analysed accurately as a pooled sample. High levels of extra-genital infections were found with 12.7% of CT infections being missed on VVS. Trebling diagnostic costs with rectal, pharyngeal, and VVS samples would be unaffordable for many health systems but a pooled sample has the same laboratory cost as the current VVS. Disclosure of interest statement: Dr Janet Wilson has received honoraria and travel and accommodation expenses from BD Diagnostics, and research grants in the form of diagnostic kits from Hologic/Gen-Probe.